Death of Murad Hofmann: Some thoughts and recollections - Hasan, Md. Mahmudul (2020)
Born a Catholic in Germany’s Aschaffenburg, Hofmann began his university education at Union College in New York in 1951. Then he studied law at Munich and Harvard Universities with a PhD in jurisprudence from the former in 1957 and a Master of Law from Harvard Law School in 1960. A prolific author of about a dozen books and an eloquent speaker, Hofmann embraced Islam in 1980, performed hajj in 1992 and describes his hajj experiences and his thoughts and reflections on various aspects of Islam in Journey to Makkah.